3rd International Symposium on Image and Signal Processing and Analysis, 2003. ISPA 2003. Proceedings of The
DOI: 10.1109/ispa.2003.1296898
|View full text |Cite
|
Sign up to set email alerts
|

Compression of IP images for antostereoseopic 3d imaging applications

Abstract: An Autostereoscopic 3 0 viewing .system that operates on the principles of Integral PhotographyIP provides a imique sen.se of depth. full parallax and multi-view functionality. The inherent redundancy of these images results into great amounts of data that should be efficiently coded for transmission or storage operations. In this communication a method for efficient coding of such images is presented, targeting to 3 0 imaging but video applications. The method is based on common techniques broadly used in ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 8 publications
(2 reference statements)
0
26
0
2
Order By: Relevance
“…The single most adopted method to assess quality of IIpictures, and other 3D-image formats, is to globally apply the Peak Signal to Noise Ratio (PSNR) metric to the complete data set of pixels [8]- [11]. The advantage is that single scalar value are produced that aggregates the quality of the whole II-picture; lending itself well to comparative studies.…”
Section: Iii-b Evaluation Methodsmentioning
confidence: 99%
“…The single most adopted method to assess quality of IIpictures, and other 3D-image formats, is to globally apply the Peak Signal to Noise Ratio (PSNR) metric to the complete data set of pixels [8]- [11]. The advantage is that single scalar value are produced that aggregates the quality of the whole II-picture; lending itself well to comparative studies.…”
Section: Iii-b Evaluation Methodsmentioning
confidence: 99%
“…[3][4][5][6][7][8] This has the advantage of producing a result that in a single scalar value aggregates the quality of the complete data set of the 3D-image. Hence, it lends itself well to comparative studies where a single measurement using the metric also give rise to a single value.…”
Section: Previous Workmentioning
confidence: 99%
“…3 The set of EIs has been combined into a sequence that was then coded using a combination of JPEG-like intra-coding and MPEG-like intercoding techniques. 4 A similar approach was later proposed, where II-frames with a low number of high resolution EI was coded using the MPEG-2 video coding standard. 5 However, in our previous work we have shown that forming a sequence from EIs is not feasible for all II-structures.…”
Section: Introductionmentioning
confidence: 99%
“…This formed pseudo video sequence (PVS) is then coded using the video coding standard H.264/MPEG-4 AVC. Combined, this results in a significantly improved compression efficiency, both when compared to the EI-based PVS-scheme 4,5 as well as JPEG 2000 coding of the full II-frame.…”
Section: Introductionmentioning
confidence: 99%